Validity of the Electronic Whisper Sound Test as a Screening Method in School-aged Children - Irma Zakina; Nyilo Purnami; In Seok Moon (Wolters Kluwer - Medknow Publications, 2023)
Introduction: The whisper test is one of the several simple methods to detect hearing loss in children and adults. The electronic whisper sound test is a new tool for detecting hearing loss early, and research has yet to be conducted in Indonesia. This study aimed to determine the validity of the electronic whisper sound test as a screening method in school-aged children at the Outpatient Unit of Dr. Soetomo General Academic Hospital. Methods: This type of study used a retrospective research design by conducting an electronic whisper test as a hearing screening in school-aged children between the age group of 6 and 18 years who visited the Audiology Outpatient Unit of Dr. Soetomo General Academic Hospital for 6 months from October 2021 to March 2022. Results: Based on the patient visit data, 32 patients were randomly selected from the population who met the inclusion criteria. The critical electronic whisper sound test results were compared with the pure-tone audiometry as a gold standard hearing screening, with a sensitivity value of 92%, specificity of 78.8%, positive predictive value of 53.3%, and negative predictive value of 88.3%. Conclusion: Hearing screening is critical, especially for school-aged children, because it determines language and speech development. A simple procedure can be done through a whisper test, which in its development can be an electronic whisper test. Besides being easy and efficient, this tool does not require special skills.